PANDANGAN ISLAM TENTANG ILMU EKONOMI DAN SISTEM EKONOMI - Sri Maharani (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2022)
Economics and economic systems discuss economics, but economics and economic system are two different things. Where between the concept of one with the concept of the other is not the same. Because the economic system is not distinguished on the basis of wealth and wealth, it is not even affected by wealth. Therefore, it is a fatal mistake, when making the economy as a discussion which is considered to discuss the same problem between science and economic system. Because of that kind of thing, it will certainly lead to errors in understanding the economic problems to be solved. Islam's view of the issue of wealth differs from the Islamic view of the issue of the use of wealth